RESEARCH OF STUDENTS 'DEVELOPMENT LEVELS FOLKLORE AS THE FIRST BASIS OF PEOPLE'S PEDAGOGY - V.N. Lykov (Academy of Cognitive and Natural Sciences, 2000)
In this article on the basis of the experimental work among pupils and teachers from three regions of Ukraine the levels of assimilation of folklore, the indexes, criteria, and features of the given levels are determined. It is an important condition of the increasing of the national self-identification of pupils.